2014
DOI: 10.1007/s12020-013-0137-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of high-normal serum TSH levels on major cardiovascular risk factors and Visceral Adiposity Index in euthyroid type 2 diabetic subjects

Abstract: Although several observations indicate that serum TSH levels in the high normal range are related to cardiovascular (CVD) risk factors in the general population, similar data are limited in diabetic subjects. The aim of this study was to investigate the potential associations between TSH serum levels within the normal range and major metabolic and non-metabolic CVD risk factors in a cohort of euthyroid type 2 diabetic subjects. Thyroid hormones, TSH levels, anthropometric parameters, lipid profile, glucose con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 36 publications
3
21
2
Order By: Relevance
“…Taken together, our data suggest that the increased expression of TSHR and NIS in obese rats could maintain normal T4 production, even with reduced TSH serum levels. However, we cannot discard that the persistence of the obese state could lead to a future thyroid failure/impairment and a corresponding increase in TSH levels (Ruhla et al 2010;Giandalia et al 2014;Lee et al 2015). Lee et al (2015) reported increased TSHR, NIS, TPO, and TG mRNA content in high-fat diet-induced obese mice but, differently of our results, they showed increased TSH levels.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…Taken together, our data suggest that the increased expression of TSHR and NIS in obese rats could maintain normal T4 production, even with reduced TSH serum levels. However, we cannot discard that the persistence of the obese state could lead to a future thyroid failure/impairment and a corresponding increase in TSH levels (Ruhla et al 2010;Giandalia et al 2014;Lee et al 2015). Lee et al (2015) reported increased TSHR, NIS, TPO, and TG mRNA content in high-fat diet-induced obese mice but, differently of our results, they showed increased TSH levels.…”
Section: Discussioncontrasting
confidence: 79%
“…Although there are reports establishing a relationship between obesity and thyroid disorders, this issue still remains unclear. Reduced thyroid function has been observed in obese individuals (Ruhla et al 2010;Giandalia et al 2014). Moreover, increased serum thyrotropin (TSH), elevated triglycerides concentrations, and waist circumference were positively correlated in obese children (Shalitin et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that BMP-4 levels were significantly higher in obesity with slight increased TSH than without increased TSH. Central obesity is associated with SH, especially the visceral fat deposition is related to increased TSH [37, 38]. Therefore, it may be the increased TSH with more serious visceral fat deposition that caused the higher BMP-4 levels in this study.…”
Section: Discussionmentioning
confidence: 77%
“…It places a spotlight on the gut-brain axis as a control system regulating energy metabolism. 13 Recently, Lee et al 14 identified an association between F I G U R E 2 RT-PCR validation of genes co-regulated in the simple obese (OB) and obese plus type 2 diabetes (OD) groups compared with the control (CON) group. In this study, we analyzed human gastric mucosa tissue samples to identify diseaserelated genes and pathways using a gene microarray and RT-PCR.…”
Section: Discussionmentioning
confidence: 99%